EARLY DETECTION OF GREY MOULD DEVELOPMENT IN ‘RED GLOBE’ GRAPES DURING STORAGE - W. Q. Guan; X. L. Wu; R. X. Yan; Z. D. Wang; X. T. Wang (Journal of Animal and Plant Sciences, 2015)
The monitoring of volatile compounds generated by diseased fruits and vegetables has been investigated as a means of detecting infections in storage compartments. To evaluate if infections of Botrytis cinerea could be detected prior to obvious disease symptoms on table grapes, the disease severity were assessed and the production of carbon dioxide, ethylene, ethanol, and acetaldehyde by ‘Red Globe’ grapes was measured by gas chromatography during storage at 20 °C following inoculation with B. cinerea as a spore suspension. The results indicated that visible decay became obvious between days 2 and 3 after inoculation, and a marked increase in ethylene production could be detected more than 24 h before the onset of the first signs of decay. However, a marked increase in carbon dioxide and ethanol was evident only on day 3 after inoculation and was correlated with decay development, whilst acetaldehyde could not be detected. It is estimated that ethylene could serve as an early indicator of infection of B. cinerea infection in table grapes, and may be used to predicate the presence of decayed table grapes and other fresh fruits during storage and transportation.
Keywords: Botrytis cinerea; Postharvest; Red Globe grape; Decay; Prediction